INFECTIOUS ENTEROTOXEMIA DISEASE OF SHEEP DIAGNOSTICS AND PREVENTION - Klichov Odil Ilkhomovich; Salimov Ilkhom Khaitovich (Journal of Medical Genetics and Clinical Biology, 2024)
The article describes the diagnosis of infectious enterotoxemia of sheep, the epizootic state of the disease, the course and manifestation of clinical symptoms, and the identification of characteristic pathological changes. Isolation of the causative agent and diagnosis based on laboratory studies with bioassay results in susceptible laboratory animals. Information on the prevention of infectious enterotoxemia of sheep is provided